Japan’s Aging Society: A Challenge to Japan’s Diversity & Social Inclusion - Fransisca Fleicia Paschaline; Rama Ardhia Prastita; Ericka Mega (Jurnal Transformasi Global, 2023)
Japan is a super-aged society. The combination of high life expectancy and low fertility rates leads to a decreasing population. The situation is so chronic that at the extreme consequences, Prime Minister Fumio Kishida warned Japan was "on the brink of not being able to function as a society." Based on this issue, the article aims to discuss and examine how Japan's demographic crisis affects diversity and social inclusion in economic, social, and political life and what policies should be enforced to create a more diverse and inclusive society in Japan. It is an important topic as no existing literature comprehensively examines how the aging society directly impacts diversity and social inclusion. This paper uses the concept of shrinkanomics, which describes the troublesome economic development in Japan due to its shrinking population, and the theory of inclusive social development, which emphasizes that sustainable development can only be achieved if all members of a society are included. This paper argues that an aging society significantly impacts the political issue of strict immigrant policies and Japan's identity, the economic gap between generations, and the social issue of the healthcare system. To address these issues, the authors argue that there is a need for sustainable policy by pursuing a proactive approach to immigration, enhancing public-private partnerships to promote inclusive economic innovation, and strengthening the home and community-based care system. Keywords: Aging society; diversity; inclusivity; Japan; shrinkanomics.